2011
DOI: 10.1186/bcr2943
|View full text |Cite
|
Sign up to set email alerts
|

Persistent upregulation of U6:SNORD44 small RNA ratio in the serum of breast cancer patients

Abstract: IntroductionSerum microRNAs have the potential to be valuable biomarkers of cancer. This investigation addresses two issues that impact their utility: a) appropriate normalization controls and b) whether their altered levels persist in patients who are clinically free of the disease.MethodsSera from 40 age-matched healthy women and 39 breast cancer patients without clinical disease at the time of serum collection were analyzed for microRNAs let-7f, miR-16, miR-21 and miR-155 using quantitative real-time PCR. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 36 publications
(56 reference statements)
6
101
0
Order By: Relevance
“…The spliceosome complex, which catalyzes pre-mRNA splicing, and in which U6 is a key functional component, is frequently deregulated in a wide variety of cancers [30]. Consistent with this and with our findings, it has been shown that serum RNU6-1 levels are differentially expressed in serum from individuals with breast cancer compared to healthy controls [31]. In addition, a recent miRNA profiling study performed on the serum exosomes in individuals with glioblastoma identified RNU6-1 as a potential diagnostic cancer biomarker [32].…”
Section: Discussionsupporting
confidence: 80%
“…The spliceosome complex, which catalyzes pre-mRNA splicing, and in which U6 is a key functional component, is frequently deregulated in a wide variety of cancers [30]. Consistent with this and with our findings, it has been shown that serum RNU6-1 levels are differentially expressed in serum from individuals with breast cancer compared to healthy controls [31]. In addition, a recent miRNA profiling study performed on the serum exosomes in individuals with glioblastoma identified RNU6-1 as a potential diagnostic cancer biomarker [32].…”
Section: Discussionsupporting
confidence: 80%
“…The relationship of PR status and miR-155 expression is unresolved, with 2 studies reporting contradictory results (27,29). The topic of serum miRNAs is also somewhat controversial, with some studies suggesting that serum miRNA levels are robust (35,36), and others claiming that the miRNAs often used as normalization controls are highly variable in sera samples and thus miRNA quantification in sera is not reproducible (37). This suggests analysis of serum alone is not sufficient to determine whether miR-155 is differentially expressed.…”
Section: Clinical Relevance Of Mir-155 In Breast Cancermentioning
confidence: 99%
“…Intriguingly, in TIC xenografts of mice, knock down of SNORA42 resulted in a decrease of tumorigenesis (46). In other cancer cell lines, it has been identified that SNORD33, SNORD44, SNORD66, and SNORD76 are upregulated, and a depletion of their expression decreases both cancer cell growth and colony formation (47,48). Regarding snoRNA downregulation that is related to tumorigenesis, human U50 box C/D snoRNA (also called SNORD50) is mutated and downregulated in prostate and breast cancers (49,50).…”
Section: Deregulation Of Snorna Biogenesis In Tumorigenesismentioning
confidence: 99%